Megapool S.A.: reconstructing a construction company - Arbaiza, Lydia (Universidad ESAN. ESAN Ediciones, 2004)
Megapool Ltd. is a family business located in Lima, Peru, specializing in the construction of Jacuzzis and saunas. It was created in 1987 to develop general activities in the field of construction and construction supervision, import, distribute and sell materials and accessories and perform other economic activities permitted by Peruvian law. In August 1999, its CEO sought a consultant to reorganize the company and solve its financial problems, as well as to face the growth stage of the business. The consultant must be able to develop a proposal for the reorganization of the company, which implies the analysis of the main areas of the company, as well as the situation of human resources.

Megapool S.A. es una empresa familiar localizada en Lima Perú y especializada en la construcción de jacuzzis y saunas. Fue creada en 1987 para desarrollar actividades generales en el rubro de la construcción y supervisión de construcción importar distribuir y vender materiales y accesorios y desempeñar otras actividades económicas permitidas por la ley peruana. En agosto de 1999 su presidente ejecutivo buscaba un consultor para reorganizar la empresa y resolver sus problemas financieros así como para enfrentar la etapa de crecimiento del negocio. El consultor debe estar en condiciones de desarrollar una propuesta para la reorganización de la empresa lo que implica el análisis de las principales áreas de la empresa así como la situación de los recursos humanos.
Keywords: Family businesses; Building; Empresas familiares; Construcción; Entrepreneurship; Emprendimiento; https://purl.org/pe-repo/ocde/ford#5.02.04